2015
DOI: 10.1590/0104-1169.0174.2549
|View full text |Cite
|
Sign up to set email alerts
|

Association between overweight and characteristics of young adult students: support for nursing care

Abstract: OBJECTIVE: to verify associations between overweight and the characteristics of young adult students to support nursing care. METHOD: case-control study conducted with young adults from public schools. The sample was composed of 441 participants (147 cases and 294 controls, with and without excess weight, respectively). Sociodemographic and clinical characteristics were collected together with exposure factors and anthropometrics. Multiple logistic regression was used. The study received Institutional Review B… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
8
0
7

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 11 publications
(17 citation statements)
references
References 12 publications
2
8
0
7
Order By: Relevance
“…This fact should not be overlooked or treated superficially by the health services 18 . In its turn, obesity increases the risk of developing stroke 19 , regardless of age, as it is related to higher incidence of obstructive sleep apnea in this population.…”
Section: Discussionmentioning
confidence: 96%
“…This fact should not be overlooked or treated superficially by the health services 18 . In its turn, obesity increases the risk of developing stroke 19 , regardless of age, as it is related to higher incidence of obstructive sleep apnea in this population.…”
Section: Discussionmentioning
confidence: 96%
“…According to Santiago et al (4) and Florêncio (21) , there are determinants of overweight that are associated with markers of family dimension and clinical and interpersonal questions. Thus, the multi-determination of this health condition is confirmed and we understand the need for a complex and solution-based health care network.…”
Section: Discussionmentioning
confidence: 99%
“…There is evidence of an increase in the prevalence of OW in adolescents and adults in general. Additionally, in the few studies performed with young adults, the frequency of cases of overweight was found to already affect a third of them (2)(3)(4) , a percentage that varies according to regional aspects. These differences show cultural particularities and the several determinants and conditioning factors involved in this intriguing problem that needs to be approached from different perspectives.…”
Section: Introductionmentioning
confidence: 99%
“…Debido a que la obesidad infantil constituye un factor de riesgo de obesidad en adultos [57][58][59] y de enfermedades metabólicas como hipertensión arterial, dislipidemias y diabetes [60,61], problemas que disminuyen la calidad de vida e incrementan gastos de salud individual y pública, es importante disponer de un indicador para detectar su presencia en forma temprana. Si bien los tres métodos de medición evaluados pueden ser útiles para determinar obesidad, el r-CT parece ser un índice preciso y tiene la ventaja de que no varía con edad, sexo, y estado puberal [62,63].…”
Section: R-ct Imc Y CC Como Indicadores De Obesidadunclassified